α-Hemoglobin-stabilizing Protein (AHSP) Perturbs the Proximal Heme Pocket of Oxy-α-hemoglobin and Weakens the Iron-Oxygen Bond - Dickson, Claire F. (American Society for Biochemistry and Molecular Biology, 2013)
α-Hemoglobin (αHb)-stabilizing protein (AHSP) is a molecular chaperone that assists hemoglobin assembly. AHSP induces changes in αHb heme coordination, but how these changes are facilitated by interactions at the αHb·AHSP interface is not well understood. To address this question we have used NMR, x-ray absorption spectroscopy, and ligand binding measurements to probe αHb conformational changes induced by AHSP binding. NMR chemical shift analyses of free CO-αHb and CO-αHb·AHSP indicated that the seven helical elements of the native αHb structure are retained and that the heme Fe(II) remains coordinated to the proximal His-87 side chain. However, chemical shift differences revealed alterations of the F, G, and H helices and the heme pocket of CO-αHb bound to AHSP. Comparisons of iron-ligand geometry using extended x-ray absorption fine structure spectroscopy showed that AHSP binding induces a small 0.03 Å lengthening of the Fe-O(2) bond, explaining previous reports that AHSP decreases αHb O(2) affinity roughly 4-fold and promotes autooxidation due primarily to a 3–4-fold increase in the rate of O(2) dissociation. Pro-30 mutations diminished NMR chemical shift changes in the proximal heme pocket, restored normal O(2) dissociation rate and equilibrium constants, and reduced O(2)-αHb autooxidation rates. Thus, the contacts mediated by Pro-30 in wild-type AHSP promote αHb autooxidation by introducing strain into the proximal heme pocket. As a chaperone, AHSP facilitates rapid assembly of αHb into Hb when βHb is abundant but diverts αHb to a redox resistant holding state when βHb is limiting.